Electronic and structural characterization of InN heterostructures grown on β-LiGaO2 (001) substrates. (September 2015) - Wang, Jianli; Pu, Long; Tang, Gang; Zhang, Junting
Abstract: The structural and electronic properties of a wurtzite InN (11–20) film on an orthorhombic LiGaO2 (001) substrate were systematically studied by first-principle calculations. The In adsorption atoms are more favorable than the N atoms, the N–N dimer will be formed with increasing N coverage on LiGaO2 (001) surface. The calculated surface grand potentials show the perfect O2 -termination is more stable than those defective O2 -terminated LiGaO2 (001). The InN/O2 -terminated LiGaO2 (001) interface is energetically favorable interface among the atomic arrangements of the InN (11–20)‖LiGaO2 (001) interfaces. The antisite defects InN may act as a potential source for p -type behavior of InN on the O2 -terminated LiGaO2 (001) surface. Highlights: The In or N adsorption atoms are more favorable O2 -termination LiGaO2 (001). The In adsorption atoms are more favorable than the N atoms for the LiGaO2 (001). The N–N dimer will be formed with increasing N coverage on LiGaO2 (001) surface. The defective O2 -termination is unstable for the LiGaO2 (001) surface. The InN and VN defects reduce the occupied states at the InN/LiGaO2 interface.